2019
DOI: 10.3390/nano9010060
|View full text |Cite
|
Sign up to set email alerts
|

Glancing-Angle Deposition of Nanostructures on an Implant Material Surface

Abstract: Cell-compatible and antibacterial surfaces are needed for implants, which frequently have complex and rough surfaces. Bio-inspired columnar nanostructures can be grown on flat substrates; however, the application of these nanostructures on clinically relevant, complex, and rough surfaces was pending. Therefore, a titanium plasma spray (TPS) implant surface was coated with titanium nano-spikes via glancing angle magnetron sputter deposition (GLAD) at room temperature. Using GLAD, it was possible to cover the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The titanium plasma spray (TPS) can be considered another well-established medical technology for improving surface roughness and wettability [ 40 ]. In general, a TPS surface structure is very rough (macro-roughness of up to 240 µm and micro-roughness approximately 40 μm) [ 41 ], as it is formed by overlapping droplets of solidified Ti [ 42 ], and is characterized by the occurrence of cavities, niches, clefts, and curved areas, resulting in a porous-like appearance.…”
Section: Discussionmentioning
confidence: 99%
“…The titanium plasma spray (TPS) can be considered another well-established medical technology for improving surface roughness and wettability [ 40 ]. In general, a TPS surface structure is very rough (macro-roughness of up to 240 µm and micro-roughness approximately 40 μm) [ 41 ], as it is formed by overlapping droplets of solidified Ti [ 42 ], and is characterized by the occurrence of cavities, niches, clefts, and curved areas, resulting in a porous-like appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Several microbiology and stem cell studies using nanospikes fabricated using GLAD on titanium substrates have been published recently [102][103][104][105]. Zeigler et al reported promising bactericidal effects of the nanospikes against E. coli and a significant improvement in promoting the osteogenic response of hMSCs compared to plasma roughened TiO 2 surfaces [105]. Motemani et al reported different levels of hMSC growth on slanted, chevron and vertical structures on TiO 2 substrate [102].…”
Section: Glancing Angle Depositionmentioning
confidence: 99%
“…These are crucial aspects for an actual device using nanostructures arrays fabricated by GLAD being introduced in the market. In fact, two different works have recently reported the use of glancing angle deposition with magnetron sputtering (MS-GLAD) to cover the surface of real implants with antibacterial nanostructured coatings [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%